Sustainable Careers of Self-Initiated Expatriates in Kokkola :The Role of Context and Personal Resources - Lehojärvi, Emmi (My University, 2026)
The aim of this Master’s thesis is to examine how contextual factors in the Kokkola region, as well as individual-level resources and agency, influence the career sustainability of international talents belonging to the group of self‑initiated expatriates. The starting point of the study lies in the rapid transformation of working life, globalization, and the shortage of skilled labor, all of which highlight the need to understand how international employees can build long-term sustainable career paths. The research draws on sustainable career theory, which defines career sustainability through health, happiness, and productivity, and emphasizes the dynamic and context-dependent nature of careers. In this thesis, the focus is placed on both the contextual and individual dimensions of the model, allowing the analysis to consider the structural conditions of the environment as well as the resources and agency of SIE individuals. Key concepts include self‑initiated expatriates (SIE), career sustainability, and contextual and individual-level factors examined at the institutional, organizational, social, and private-life levels. Previous research shows that SIE individuals operate without organizational support, which increases their dependence on local labor markets, administrative processes, and social networks. According to sustainable career theory, context and the individual are not background factors but active elements that together enable or constrain long-term career development. The study was conducted as qualitative research, and the data were collected through semi-structured interviews with SIE individuals working in Kokkola. The data were analyzed using theory-driven content analysis, which made it possible to examine contextual and individual-level factors in relation to the three indicators of career sustainability. In conclusion, the study shows that the career sustainability of SIE individuals is shaped by the interaction between contextual conditions and individual-level resources, and that regional circumstances as well as personal agency can either support or limit international talents’ opportunities to build a sustainable career. The research provides new empirical knowledge about the labor market and settlement context of the Kokkola region and offers practical recommendations for employers and policymakers. While the qualitative approach and regional focus limit the generalizability of the findings, they provide an in-depth understanding of SIE individuals’ experiences within the local operating environment.

Tämän pro gradu -tutkielman tavoitteena on tarkastella, miten Kokkola-alueen kontekstuaaliset tekijät sekä yksilötason voimavarat ja toimijuus vaikuttavat self-initiated expatriates -ryhmään kuuluvien kansainvälisten osaajien urien kestävyyteen. Tutkimuksen lähtökohtana on työelämän nopea muutos, globalisaatio ja osaajapula, jotka korostavat tarvetta ymmärtää, miten kansainväliset työntekijät voivat rakentaa pitkän aikavälin kestäviä urapolkuja. Tutkimus nojaa sustainable career -teoriaan, joka määrittelee uran kestävyyden terveyden, onnellisuuden ja tuottavuuden kautta sekä korostaa urien dynaamisuutta ja kontekstisidonnaisuutta. Tässä tutkielmassa tarkastelu kohdistuu sekä mallin konteksti- että yksilödimensioihin, jolloin analyysi huomioi sekä ympäristön rakenteelliset olosuhteet että SIE-henkilöiden omat resurssit ja toimijuuden. Keskeisiä käsitteitä ovat self-initiated expatriates (SIE), urakestävyys sekä kontekstuaaliset ja yksilötason tekijät, joita tarkastellaan institutionaalisella, organisatorisella, sosiaalisella ja yksityiselämän tasolla. Aiempi tutkimus osoittaa, että SIE-henkilöt toimivat ilman organisaation tarjoamaa tukea, mikä lisää heidän riippuvuuttaan paikallisista työmarkkinoista, viranomaisprosesseista ja sosiaalisista verkostoista. Sustainable career -teorian mukaan konteksti ja yksilö eivät ole taustatekijöitä, vaan aktiivisia elementtejä, jotka yhdessä mahdollistavat tai rajoittavat pitkän aikavälin urakehitystä. Tutkimus toteutettiin laadullisena tutkimuksena, ja aineisto kerättiin puolistrukturoiduilla haastatteluilla Kokkolassa työskenteleviltä SIE-henkilöiltä. Aineisto analysoitiin teoriaohjaavan sisällönanalyysin avulla, mikä mahdollisti kontekstuaalisten ja yksilötason tekijöiden tarkastelun suhteessa urakestävyyden kolmeen indikaattoriin. Johtopäätöksenä tutkimus osoittaa, että SIE-henkilöiden urakestävyys rakentuu kontekstuaalisten olosuhteiden ja yksilötason voimavarojen yhteisvaikutuksesta, ja että alueelliset olosuhteet sekä henkilökohtainen toimijuus voivat joko tukea tai rajoittaa kansainvälisten osaajien mahdollisuuksia rakentaa kestävää uraa. Tutkimus tuottaa uutta empiiristä tietoa Kokkolan alueen työmarkkina- ja asettautumiskontekstista sekä tarjoaa käytännön suosituksia työnantajille ja päätöksentekijöille. Laadullinen tutkimusote ja alueellinen rajaus rajoittavat tulosten yleistettävyyttä, mutta tarjoavat syvällisen ymmärryksen SIE-henkilöiden kokemuksista paikallisessa toimintaympäristössä.
Keywords: career; career development; expatriates; sustainable development; working abroad; career planning; labour market; career choice; professional development; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business